Association Between Gut Microbiota and Depressive Symptoms: A Cross-Sectional Population-Based Study in South Korea. Issue 7 (18th September 2022) - Kim, Sun-Young; Park, Eunkyo; Lim, Weon-Jeong; In Kim, Soo; Jeon, Sang Won; Chang, Yoosoo; Ryu, Seungho; Kim, Hyung-Lae; Kim, Han-Na
ABSTRACT: Objective: This study aimed to investigate the association between gut microbiota and depressive symptoms in a large population cohort of Korean adults. Methods: Overall, 1238 participants were included in the study. Participants were categorized into depressed or non-depressed groups, based on the depressive symptoms reported on the Center for Epidemiologic Studies Rating Scale for Depression, with a cutoff score of 16, and their fecal microbiota was profiled using 16S ribosomal RNA gene sequencing. Several alpha and beta diversity measures were also estimated. The association between depressive symptoms and gut microbiota was analyzed using generalized linear models. The inferred function of the metagenomes was compared between the two groups. Results: There were no consistent differences in alpha and beta diversity between the depressed and non-depressed groups. However, the continuous measure of depressive symptoms was inversely associated with one of four measures of alpha diversity (Shannon's diversity, p = .021). We also found a substantial difference between the depressed and non-depressed groups in the Bray-Curtis dissimilarity among the four beta diversity indices ( p = .004). Participants whose depressive symptoms exceeded a clinical cutoff score had a lower relative abundance of the genus Faecalibacterium when compared with controls (coefficient = −0.025, q = 0.047). However, the depressed group had a significantly higher abundance of the genus Oscillospira than did the non-depressed group (coefficient = 0.002, q = 0.023). Conclusions: Our findings contribute to the identification of potential relationships between the gut microbiota and depressive symptoms and provide useful insights for developing microbiota-based interventions for patients with depressive symptoms.